Haptic exploration of plateware alters the perceived texture and taste of food - Biggs, L; Juravle, G; Spence, C (Elsevier, 2016)
We report two naturalistic citizen science experiments designed to highlight the influence of the texture of plateware on people's rating of the mouthfeel and taste of food (specifically, biscuits) sampled from that plateware. In the first experiment, participants tasted a biscuit from a pair of plates, one having a rough and the other a smooth finish. In the second experiment, participants tasted biscuits and jelly babies; participants rated the mouthfeel and taste of the two foodstuffs. The results both confirm and extend previous findings suggesting that haptically and visually perceived texture can influence both oral-somatosensory judgments of texture as well as, in this case, the reported taste or flavour of the food itself. The crossmodal effects reported here are explained in terms of the notion of sensation transference. These results have potentially important implications for everything from the design of the tactile aspects of packaging through to the design of serviceware in the setting of the restaurant.